Estrategia de publicidad de la empresa Davis Languis Solution de la ciudad de Guayaquil periodo de 2023. - Bajaña Mora, Betzaida Adalguisa (2025)
The topic of this research work is: Advertising strategy of the company Davis languis solution of the city of Guayaquil, period of 2023 "and its main objective is: "Analyze the Advertising strategy of the company Davis languis solution of the city of Guayaquil" which will be necessary to achieve a positioning in the market in addition to attracting customers and building loyalty to the brand. This work was carried out in the aforementioned company. The “inductive-deductive” methodology was used, using tools such as surveys to give us an in-depth account of how much they know this type of service offered by the company “Davis languis solution”, advertising strategies were proposed such as logo redesign, summary of activities to be carried out, social network design, advertising formats for the different platforms to be used. “Davis languis solution” is a medium-sized institution with a low influx of students and few contracts. Due to its lack of advertising, and the way of segmenting, problems are arising in the institution, on which we are going to work by focusing on improving its strategies to attract clients and that its profits continually improve in such a way that “Davis languis solution” achieves its stated goals and objectives. By having a correct segmentation we will know which audience to target, that is, we will know our target audience and our potential clients who will be interested in what we do and we will be able to get business, as well as grow on social networks to attract small clients and retain them to the brand and thus word of mouth marketing can arise, which is our best advertising, providing complete and quality work with the best service and customer service, which is our commercial policy, since if the client feels good, they will return to us. business and how we are going to achieve it, well we are going to interact on social networks since currently the first place to look for a service is on the Internet and on social networks where the user will observe trust through their number of followers, good comments and experiences of other clients. You must find all this in our networks and we will work on it, since you currently do not have these commercial strategies, your followers are few and your interaction with them is minimal, and if you apply them it will allow you to improve the company in the market and be competitive.